Valentine's Day sweets and treats - Owen, Ruth, 1967- (New York : Windmill Books, 2013)
Contains recipes with step-by-step instructions for making Valentine's Day treats, including cookies, cupcakes, and chocolate-dipped strawberries.
A festival of treats, sweets, and love -- Before you begin cooking -- Easy Valentine's rocky road -- I love you cookies -- Ti amo linguine! -- Frozen strawberry yogurt dessert -- Red velvet cupcakes -- Super strawberry slushies -- Chocolate-dipped strawberries.
Includes index.
6.3
3-6
Keywords: Valentine's Day cooking -- Juvenile literature; Desserts -- Juvenile literature; Valentine's Day cooking; Desserts; Cookbooks; Cooking